Ability of a single question to discriminate physical and psychological problems relating to the fear of fall in hyperkyphosis older adults - Multakorn, Sirirut; Namwong, Wilairat; Thaweewannakij, Thiwabhorn (Archives of Allied Health Sciences, 2025)
Fear of falling (FOF) is a significant concern among older adults, especially those with hyperkyphosis that may induce several negative impacts, such as reduced both physical and social interaction, increased risk of future falls and associated mortality, and decreased quality of life. Given these consequences, early and accurate identification of FOF is essential to inform targeted preventive strategies. Various assessment tools are available to evaluate FOF, including single-item question, self-reported scales such as the Falls Efficacy Scale-International (FES-I), and objective assessments, including the five times sit-to-stand test (FTSST). However, a universally accepted gold standard for assessing FOF in older adults with hyperkyphosis has not yet been established. This study aimed to evaluate whether a single-question assessment can effectively identify individuals with and without FOF, using the FES-I and FTSST as reference measures. Sixty-three community-dwelling older adults aged 60 years and above with clinically confirmed hyperkyphosis participated in the study. All participants were assessed for FOF using the single-question method to divide the participants into non-FOF and FOF groups. Then they were assessed for physical and psychological problems relating to FOF using the FES-I and FTSST. The results indicated that participants in the FOF group had significantly higher FES-I scores than those in the non-FOF group (p-value < 0.001). Similarly, participants with FOF required significantly more time to complete the FTSST (p-value < 0.001). These findings suggested that the single-question assessment can effectively distinguish individuals with FOF from those without FOF. In conclusion, the single-question approach appears to be a simple, time-efficient, and practical screening tool for identifying FOF in older adults with hyperkyphosis. Its implementation in clinical and community settings may contribute to early detection and timely intervention, potentially reducing fall risk and enhancing functional outcomes in this population.